Do the Characteristics of the Board of Directors Affect Earnings Management in State-Owned Enterprises? - Dani, Ni Komang Trisma; Widhiastuti, Ni Luh Putu; Rustiarini, Ni Wayan (Journal of Culture Accounting and Auditing, 2026)
This study aims to examine the effect of board size, board education, board gender, board political connection, and board narcissism on earnings management in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2021–2023 period. This research is grounded in agency theory, which explains that differences in interests between principals and agents may encourage opportunistic behavior, including earnings management. The population consisted of all SOEs listed on the Indonesia Stock Exchange, and the sample was selected purposively, yielding 24 companies with 72 firm-year observations. Secondary data were obtained from annual reports and analyzed using multiple linear regression. The results indicate that board size, board education, board gender, and board political connection do not significantly affect earnings management. In contrast, board narcissism has a positive and significant effect on earnings management. These findings suggest that board members’ personal characteristics play a more important role in influencing earnings management practices than the board’s structural characteristics. This study contributes to the corporate governance literature by highlighting the importance of behavioral factors, particularly board narcissism, in explaining earnings management practices within Indonesian SOEs.